Effect of FIFA11+ level 3 on balance and agility of young adult football players - Kamal, Daniel Haqim; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor; Shari, Maisarah; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the impact of the FIFA 11+ Level 3 protocol on the neuromuscular performance of 20 young adult footballers, specifically comparing its effectiveness against traditional warm-up routines. By utilizing the Y Balance Test and Illinois Agility Test, the research analyzes within-group and between-group changes to determine how this specialized injury prevention program influences postural control and movement efficiency. The findings aim to provide actionable evidence for optimizing training strategies to enhance agility and balance in youth football players.